1997
DOI: 10.1212/wnl.48.2.363
|View full text |Cite
|
Sign up to set email alerts
|

Cabergoline in the treatment of early parkinson's disease

Abstract: Cabergoline is a potent D2 receptor agonist with a half-life of 65 hours that may provide continuous dopaminergic stimulation administered once daily. In this study, we randomized de novo Parkinson's disease (PD) patients to treatment with increasing doses of cabergoline (0.25 to 4 mg/d) or levodopa (100 to 600 mg/d) up to the optimal or maximum tolerated dose. Decreases of > 30% in motor disability (Unified Parkinson's Disease Rating Scale Factor III) versus baseline were considered indicative of clinical imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(64 citation statements)
references
References 9 publications
3
58
0
3
Order By: Relevance
“…3 Cabergoline is absorbed from the gastrointestinal tract within 0.5 to 4 h 2 and has an average elimination half-life of 65 h that may provide continuous dopaminergic stimulation when administered once daily. 8 Although the patient had delayed onset of symptoms, the long elimination half-life of cabergoline may contribute to its prolonged duration of action and persistence of symptoms even after drug withdrawal, as observed in our patient. The duration of QT interval is the major determinant of the risk of drug-induced TdP.…”
Section: Discussionsupporting
confidence: 48%
“…3 Cabergoline is absorbed from the gastrointestinal tract within 0.5 to 4 h 2 and has an average elimination half-life of 65 h that may provide continuous dopaminergic stimulation when administered once daily. 8 Although the patient had delayed onset of symptoms, the long elimination half-life of cabergoline may contribute to its prolonged duration of action and persistence of symptoms even after drug withdrawal, as observed in our patient. The duration of QT interval is the major determinant of the risk of drug-induced TdP.…”
Section: Discussionsupporting
confidence: 48%
“…Levodopa appeared to be better than cabergoline for improvement in both part II (ADL) and part III (motor) of the UPDRS, 30 but the publication does not report a statistical comparison of these data. After 4 years in the clinical trial, levodopa subjects still showed an average of 30% improvement in motor disability (part III), while patients treated with cabergoline showed a 22 to 23% improvement.…”
Section: Initiating Dopaminergic Treatment When Symptomatic Therapy mentioning
confidence: 97%
“…Adverse events were higher in the cabergoline group (75.8%) versus levodopa (65.7%), with nausea being the most common in both. 30 In the study of ropinirole versus levodopa, 6 the primary endpoint was dyskinesias rather than other types of motor complications. The absolute risk reduction for dyskinesias after 5 years of treatment was 26% for the ropinirole group (monotherapy or with the later addition of levodopa adjunctive therapy).…”
Section: Initiating Dopaminergic Treatment When Symptomatic Therapy mentioning
confidence: 99%
“…2,3) A few high-performance liquid chromatographic (HPLC) methods have been developed for the determination of CAB in plasma using electrochemical detection, 4) tandem mass spectrophotometry (TMS) [5][6][7] or triple-quadrupole mass spectrometry. 8) ROP, 4-[2-(dipropylamino)ethyl]-l,3-dihydro-2H-indol-2-one hydrochloride, is a specific D2 and D3 receptor non-ergoline dopamine agonist that is probably equally effective as L-dopa in mild, early Parkinson's disease.…”
Section: Cab N-[3-(dimethylamino)propyl]-n-(ethylamino)car-mentioning
confidence: 99%